RANCANG BANGUN ALAT PENCETAK MOTIF KERAJINAN SOUVENIR UNTUK MENINGKATKAN KUALITAS DAN PRODUKTIVITAS INDUSTRI KERAJINAN KULIT SALAK - Sabatari, Widyabakti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
The partner industry in this Vucer program is Q-Sal Accessories. The purpose is to overcome the problem faced by the partner industry, which are: 1) get the effective and efficient print tool construction of salak's pelt craft motive, 2) get the show action grade information of salak's pelt craft motive  of  vucer  result,  3)  improve  the  quality  and  productivity of the souvenir that produced by Q-Sal Accessories industry. The  methods  used  to  handle  this  problem  are:  a)  field  survey to observe the process of souvenir production in Q-Sal Accessories in Salak Pondoh Agro Wisata area, Kenteng, Wonokerto, Turi, Sleman, Yogyakarta, b) need analysis and concept making, c) design development, d) production process of print tool of salak's pelt souvenir craft motive, e) try out of print tool of salak's pelt souvenir craft motive in the partner industry. Result obtained from this programs are: a) the creation of the model of print tool of salak's pelt souvenir craft motive, b) the obtained of  the show action grade information of  salaks' pelt craft motive. Previously, scissors achieved 3-4 pieces of salak's pelt motive, while  print tool of salak's pelt souvenir craft motive attained 12-15 pieces in every minute, c) the quality improvement of salak's pelt souvenir, that are more precise, smoother, and same piece portion. The productivity increase 30% than it was, since the product output is also determined by the skill of the workers